Survey

* Your assessment is very important for improving the workof artificial intelligence, which forms the content of this project

Document related concepts
no text concepts found
Transcript
```HIGHER ORDER DERIVATIVES
Consider the function ๐(๐ฅ) = ๐ฅ 3 + ๐ฅ 2 โ 2๐ฅ + 1. Differentiating this function gives the
first order derivative. Differentiating the first derivative gives the second derivative.
Differentiating the second derivative gives the third derivative, and so on. Refer to the table
below.
Given: ๐(๐ฅ) = ๐ฅ 3 + ๐ฅ 2 โ 2๐ฅ + 1
Prime Notation
1st Order Derivative
๐โฒ(๐ฅ)
2nd Order Derivative
๐โฒโฒ(๐ฅ)
3rd Order Derivative
๐โฒโฒโฒ(๐ฅ)
4th Order Derivative
๐ (4) (๐ฅ)
5th Order Derivative
๐ (5) (๐ฅ)
.
.
.
.
.
.
.
.
๐๐กโ ๐๐๐๐๐ ๐๐๐๐๐ฃ๐๐ก๐๐ฃ๐
Ratio Notation
๐๐
๐
(๐(๐ฅ))
=
๐๐ฅ ๐๐ฅ
๐2๐
๐
(๐โฒ(๐ฅ))
=
2
๐๐ฅ
๐๐ฅ
๐3๐
๐
(๐โฒโฒ(๐ฅ))
=
3
๐๐ฅ
๐๐ฅ
๐4๐
๐๐ฅ 4
๐5๐
๐๐ฅ 5
.
.
.
.
๐ (๐) (๐ฅ)
๐ โฒ (๐ฅ) = 3๐ฅ 2 + 2๐ฅ
โ2
๐ โฒโฒ (๐ฅ) = 6๐ฅ + 2
๐ โฒโฒโฒ (๐ฅ) = 6
๐ (4) (๐ฅ) = 0
๐ (5) (๐ฅ) = 0
.
.
.
.
๐๐ ๐
๐๐ฅ ๐
๐ (๐) (๐ฅ) = 0
The 2nd, 3rd, 4th and so on up to ๐๐กโ ๐๐๐๐๐ ๐๐๐๐๐ฃ๐๐ก๐๐ฃ๐ are known as Higher Order
Derivatives. Notice that in the given function ๐(๐ฅ), the 4th order, ๐ (4) (๐ฅ), up to the nth order
derivative, ๐ (๐) (๐ฅ), the derivative is zero.
QUICK MATH FACT:
If ๐(๐) is a polynomial of degree ๐, then, the ๐๐๐ ๐๐๐๐๐ derivative is zero for ๐ โฅ ๐ + ๐. That is,
๐(๐) (๐) = ๐ ๐๐๐ ๐ โฅ ๐ + ๐
EXAMPLE 1: Find the second and third โ order derivative of the function.
2
2
1.1. ๐(๐ฅ) = 3 ๐ฅ 3 โ ๐ฅ
SOLUTION:
APPLY POWER FORMULA
2
2
๐(๐ฅ) = ๐ฅ 3 โ
3
๐ฅ
๐ โฒ(๐ฅ) = 2๐ฅ 2 +
2
๐ฅ2
๐ โฒโฒ(๐ฅ) = 4๐ฅ โ
๐ โฒ(๐ฅ) = 2๐ฅ 2 +
2
๐ฅ2
๐ โฒโฒ(๐ฅ) = 4๐ฅ โ
4
๐ฅ3
๐ โฒโฒโฒ(๐ฅ) = 4 +
4
๐ฅ3
12
๐ฅ4
1.2. ๐ฆ = ๐ฅ 2 (๐ฅ โ 1)5
SOLUTION:
APPLY PRODUCT RULE
๐ฆ โฒ = ๐ฅ(๐ฅ โ 1)4 (7๐ฅ โ 2)
๐ฆ = ๐ฅ 2 (๐ฅ โ 1)5
๐ฆ โฒ = (๐ฅ โ 1)4 (7๐ฅ 2 โ 2๐ฅ)
๐ฆ โฒ = ๐ฅ 2 [5(๐ฅ โ 1)4 ] + (๐ฅ โ 1)5 (2๐ฅ)
๐ฆ โฒโฒ = (๐ฅ โ 1)4 (14๐ฅ โ 2) + (7๐ฅ 2 โ 2๐ฅ)(4)(๐ฅ โ 1)3
๐ฆ โฒ = ๐ฅ(๐ฅ โ 1)4 [5๐ฅ + 2(๐ฅ โ 1)]
๐ฆ โฒโฒ = (๐ฅ โ 1)4 (2)(7๐ฅ โ 1) + (7๐ฅ 2 โ 2๐ฅ)(4)(๐ฅ โ 1)3
๐ฆ โฒ = ๐ฅ(๐ฅ โ 1)4 [5๐ฅ + 2๐ฅ โ 2]
๐ฆ โฒโฒ = 2(๐ฅ โ 1)3 [(๐ฅ โ 1)(7๐ฅ โ 1) + 2(7๐ฅ 2 โ 2๐ฅ)]
๐ฆ โฒ = ๐ฅ(๐ฅ โ 1)4 (7๐ฅ โ 2)
๐ฆ โฒโฒ = 2(๐ฅ โ 1)3 [7๐ฅ 2 โ 8๐ฅ + 7 + 14๐ฅ 2 โ 4๐ฅ]
๐ฆ โฒโฒ = 2(๐ฅ โ 1)3 (21๐ฅ 2 โ 12๐ฅ + 7)
๐ฆ โฒโฒ = 2(๐ฅ โ 1)3 (21๐ฅ 2 โ 12๐ฅ + 7)
๐ฆ โฒโฒโฒ = 2[(๐ฅ โ 1)3 (42๐ฅ โ 12) + (21๐ฅ 2 โ 12๐ฅ + 7)(3)(๐ฅ โ 1)2 ]
๐ฆ โฒโฒโฒ = 2[(๐ฅ โ 1)3 (6)(7๐ฅ โ 2) + (21๐ฅ 2 โ 12๐ฅ + 7)(3)(๐ฅ โ 1)2 ]
๐ฆ โฒโฒโฒ = 2(3)(๐ฅ โ 1)2 [(๐ฅ โ 1)(3)(7๐ฅ โ 2) + (21๐ฅ 2 โ 12๐ฅ + 7)]
๐ฆ โฒโฒโฒ = 6(๐ฅ โ 1)2 [(๐ฅ โ 1)(21๐ฅ โ 6) + 21๐ฅ 2 โ 12๐ฅ + 7]
๐ฆ โฒโฒโฒ = 6(๐ฅ โ 1)2 [21๐ฅ 2 โ 27๐ฅ + 6 + 21๐ฅ 2 โ 12๐ฅ + 7]
๐ฆ โฒโฒโฒ = 6(๐ฅ โ 1)2 (42๐ฅ 2 โ 29๐ฅ + 13)
1.3. ๐ฆ =
๐ฅ
โ๐ฅโ1
SOLUTION:
APPLY QUOTIENT RULE
๐ฆ=
๐ฅ
๐ฆโฒ =
โ๐ฅ โ 1
โ๐ฅ โ 1(1) โ ๐ฅ (
๐ฆโฒ =
1
)
2โ๐ฅ โ 1
โฒโฒ
๐ฆ =
2
(โ๐ฅ โ 1)
๐ฅโ2
2(๐ฅ โ 1)3/2
3
2(๐ฅ โ 1)3/2 (1) โ (๐ฅ โ 2)(2) (2) (๐ฅ โ 1)1/2
3 2
[2(๐ฅ โ 1)2 ]
1
๐ฅ
[๐ฅ โ 1 โ 2]
โ1
๐ฆ โฒ = โ๐ฅ
๐ฅโ1
๐ฆ โฒโฒ =
2(๐ฅ โ 1)3/2 โ 3(๐ฅ โ 2)(๐ฅ โ 1)1/2
4(๐ฅ โ 1)3
๐ฆ โฒโฒ =
(๐ฅ โ 1)1/2 [2(๐ฅ โ 1) โ 3(๐ฅ โ 2)]
4(๐ฅ โ 1)3
๐ฅโ2
2
๐ฆ =
(๐ฅ โ 1)3/2
๐ฆ โฒโฒ =
[2๐ฅ โ 2 โ 3๐ฅ + 6]
4(๐ฅ โ 1)5/2
๐ฅโ2
๐ฆ =
2(๐ฅ โ 1)3/2
๐ฆ โฒโฒ =
4โ๐ฅ
4(๐ฅ โ 1)5/2
2๐ฅ โ 2 โ ๐ฅ
2
๐ฆ =
(๐ฅ โ 1)โ๐ฅ โ 1
โฒ
โฒ
โฒ
๐ฆ โฒโฒ =
๐ฆ โฒโฒโฒ =
4โ๐ฅ
4(๐ฅ โ 1)5/2
5
5
4(๐ฅ โ 1)2 (โ1) โ (4 โ ๐ฅ)(4) (2) (๐ฅ โ 1)3/2
5 2
[4(๐ฅ โ 1)2 ]
5
๐ฆ โฒโฒโฒ
4(๐ฅ โ 1)2 (โ1) โ (4 โ ๐ฅ)(10)(๐ฅ โ 1)3/2
=
16(๐ฅ โ 1)5
๐ฆ โฒโฒโฒ =
โ2(๐ฅ โ 1)3/2 [2(๐ฅ โ 1) + 5(4 โ ๐ฅ)]
16(๐ฅ โ 1)5
๐ฆ โฒโฒโฒ = โ
(๐ฅ โ 1)3/2 [2๐ฅ โ 2 + 20 โ 5๐ฅ]
8(๐ฅ โ 1)5
๐ฆ โฒโฒ = โ
๐ฆ โฒโฒโฒ = โ
[18 โ 3๐ฅ]
8(๐ฅ โ 1)7/2
๐ฆ โฒโฒโฒ =
โ3(๐ฅ โ 6)
8(๐ฅ โ 1)7/2
3(๐ฅ โ 6)
8(๐ฅ โ 1)7/2
1.4. ๐(๐ฅ) = sin2 (๐๐ฅ)
SOLUTION:
APPLY POWER RULE
๐(๐ฅ) = sin2 (๐๐ฅ)
๐ โฒ (๐ฅ) = ๐ sin(2๐๐ฅ)
๐ โฒ (๐ฅ) = 2 sin(๐๐ฅ) cos(๐๐ฅ) (๐)
๐ โฒโฒ (๐ฅ) = ๐ cos(2๐๐ฅ) (2๐)
TRIGONOMETRIC IDENTITY:
๐ โฒโฒ (๐ฅ) = 2๐ 2 cos(2๐๐ฅ)
sin(2๐ฅ) = 2 sin(๐ฅ) cos(๐ฅ)
๐ โฒโฒ (๐ฅ) = 2๐ 2 cos(2๐๐ฅ)
๐ โฒ (๐ฅ) = sin(2๐๐ฅ) (๐)
๐ โฒโฒโฒ (๐ฅ) = โ2๐ 2 sin(2๐๐ฅ) (2๐)
๐ โฒ (๐ฅ) = ๐ sin(2๐๐ฅ)
๐ โฒโฒโฒ (๐ฅ) = โ4๐ 3 sin(2๐๐ฅ)
1.5. ๐2 ๐ฅ 2 + ๐ฆ 2 ๐ 2 = ๐2 ๐ 2 , find (๐)๐ฆ โฒ (๐)๐ฆ โฒโฒ (๐)๐ฆโฒโฒโฒ
SOLUTION:
APPLY IMPLICIT DIFFERENTIATION
๐2 ๐ฅ 2 + ๐ฆ 2 ๐ 2 = ๐2 ๐ 2
2๐2 ๐ฅ + 2๐ 2 ๐ฆ๐ฆ โฒ = 0
2๐ 2 ๐ฆ๐ฆ โฒ = โ2๐2 ๐ฅ
โ2๐2 ๐ฅ
๐ฆ =
2๐ 2 ๐ฆ
โฒ
๐ฆโฒ =
โ๐2 ๐ฅ
๐2๐ฆ
From ๐2 ๐ฅ 2 + ๐ฆ 2 ๐2 = ๐2 ๐ 2
๐2 ๐ 2 โ ๐2 ๐ฅ 2
๐ฆ=โ
๐2
๐ฆ=
๐โ๐ 2 โ ๐ฅ 2
๐
So,
๐ฆโฒ =
โ๐2 ๐ฅ
๐2๐ฆ
โ๐2 ๐ฅ
๐ฆโฒ =
๐2 (
๐ฆโฒ =
๐โ๐ 2 โ ๐ฅ 2
)
๐
โ๐๐ฅ
๐โ๐ 2 โ ๐ฅ 2
๐ฆโฒ =
โ๐๐ฅ
๐ฆ โฒโฒ = โ
๐โ๐ 2 โ ๐ฅ 2
๐โ๐ 2 โ ๐ฅ 2 (โ๐) โ (โ๐๐ฅ)(๐) (
๐ฆ โฒโฒ =
[๐โ๐ 2 โ ๐ฅ 2 ]
โ๐๐โ๐ 2 โ ๐ฅ 2 + ๐๐๐ฅ (
๐ฆ โฒโฒ =
โ2๐ฅ
)
2โ๐ 2 โ ๐ฅ 2
2
โ๐ฅ
)
โ ๐ฅ2
(๐ 2
๐๐
โ ๐ฅ 2 )3/2
Since, ๐ ๐๐๐ ๐ are constants, rewrite ๐ฆโฒโฒ so
that we can use POWER FORMULA instead
of QUOTIENT RULE in finding ๐ฆ โฒโฒโฒ .
โ๐ 2
๐ 2 (๐2 โ ๐ฅ 2 )
โ๐๐
[๐ 2 โ ๐ฅ 2 + ๐ฅ 2 ]
2 โ ๐ฅ2
โ๐
๐ฆ โฒโฒ =
๐ 2 (๐ 2 โ ๐ฅ 2 )
๐ฆ โฒโฒ = โ
๐ฆ โฒโฒ = โ
๐๐(๐ 2 )
5
3
๐ฆ โฒโฒโฒ = โ๐๐ (โ ) (๐ 2 โ ๐ฅ 2 )โ2 (โ2๐ฅ)
2
๐ฆ โฒโฒโฒ =
๐ 2 (๐2 โ ๐ฅ 2 )โ๐ 2 โ ๐ฅ 2
(๐ 2
๐ฆ โฒโฒ = โ๐๐(๐ 2 โ ๐ฅ 2 )โ3/2
โ3๐๐๐ฅ
(๐ 2 โ ๐ฅ 2 )5/2
๐๐
โ ๐ฅ 2 )3/2
PRACTICE PROBLEMS TO WORKOUT!
MASTERY TEST. Find the second and third โ order derivative of the function.
1
1. ๐ฆ = 3 ๐ฅ 3 โ 2๐ฅ 2 + ๐ฅ โ 10
2. ๐ฆ = 5๐ ๐ฅ
3. ๐ฆ = โ4 โ ๐ฅ 2
๐ฅ2
4. ๐ฆ = ๐ฅ+1
5. ๐ฅ 2 + ๐ฆ 2 = 1
Second โ Order Derivative.
Third โ Order Derivative.
1. ๐ฆ โฒโฒ = 2(๐ฅ โ 2)
2. ๐ฆ โฒโฒ = 5๐ ๐ฅ
4
3. ๐ฆ โฒโฒ = โ (4โ๐ฅ2 )3/2
2
1. ๐ฆ โฒโฒโฒ = 2
2. ๐ฆ โฒโฒโฒ = 5๐ ๐ฅ
12๐ฅ
3. ๐ฆ โฒโฒโฒ = โ (4โ๐ฅ2 )5/2
โ6
4. ๐ฆ โฒโฒ = (๐ฅ+1)3
4. ๐ฆ โฒโฒโฒ = (๐ฅ+1)4
1
5. ๐ฆ โฒโฒ = โ (1โ๐ฅ2 )3/2
3๐ฅ
5. ๐ฆ โฒโฒโฒ = โ (1โ๐ฅ2 )5/2
*****END OF DISCUSSION*****